Pengaruh Biaya Lingkungan Dan Kinerja Lingkungan Terhadap Roa Pada Perusahaan Energi Yang Terdaftar Di Efek Syariah (Des) Tahun 2020-2022 - Nur Fahmi; Elyanti Rosmanidar; Ferri Saputra Tanjung (E-Bisnis : Jurnal Ilmiah Ekonomi dan Bisnis, 2023)
Research Objective: This study aims to determine the effect of environmental costs and environmental performance on return on assets in energy companies listed in the Sharia Securities List. Research Design/Methodology/Approach: The research method used quantitative descriptive analysis with secondary data, analysis tools are regression panel data. Research Results: The results show that simultaneously show that the variables of environmental costs and environmental performance together have a positive and significant effect on return on assets in energy companies listed in the Sharia Securities List. while partially showing that environmental cost variables have a negative and significant effect on return on assets in energy companies listed in the Sharia Securities List, while environmental performance variables have a negative and insignificant effect on return on assets in energy companies listed in the Sharia Securities List. Implications of Research Results: The implication of research results is that companies should do the need to increase environmental costs and environmental performance in an effort to increase sustainable company profitability.